PENGARUH KEMAMPUAN BERKOMUNIKASI, PENGALAMAN KERJA, PENDIDIKAN FORMAL DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI (STUDI KASUS DI PT. BANK JATIM KANTOR CABANG PASURUAN) - rida marlita cesar mandasari; Agus Widarko; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACT This study aims to determine the effect of communication skills, work experience, formal education and work discipline on employee performance. Knowing the effect of communication skills on employee performance. Knowing the effect of work experience on employee performance. Knowing the effect of formal education on employee performance. Knowing the effect of work discipline on employee performance at PT Bank Jatim Pasuruan Branch Office.The population in this study were 92 employees of PT Bank Jatim Pasuruan Branch Office. While the sample in this study were 75 employees of PT Bank Jatim Pasuruan Branch Office as respondents. Data analysis methods in this study are validity and reliability test, normality test, classic assumption test consisting of multicollinearity and heteroscedasticity test, multiple linear regression test, hypothesis test and coefficient of determination test.The results of this study concluded that (1) communication skills has effect on employee performance (2) work experience has effect on employee performance (3) formal education has effect on employee performance (4) work discipline has effect on employee performance and (5) jointly shows that the variables of communication skills, work experience, formal education and work discipline has effect on employees performance of PT Bank Jatim Pasuruan Branch Office. Keywords : communication skills, work experience, formal education, work discipline, employee performance